Peran Organisasi Fatayat NU dalam Penyebaran Islam di Indonesia - Damayanti, Tasya Aulia (Tanjak: Sejarah dan Peradaban Islam, 2024)
This article discusses the Fatayat Nahdlatul Ulama organization in Indonesia. The Fatayat organization is one of the Nahdlatul Ulama (NU) women's organizations that moves as a form of attention to women. Fatayat NU has an important role in spreading Islam in Indonesia by forming women, teaching religious knowledge, religious moderation, and member development. In addition, this article also discusses the contribution of Fatayat NU in forming broad insights, conducting educational, social and religious activities or programs. Fatayat NU has succeeded in spreading peaceful and tolerant Islam in Indonesian society through various da'wah and social activities. Through an approach based on Islamic values, Fatayat NU can combine Islamic teachings with the socio-cultural needs of the Indonesian people. With a non-coercive approach, Fatayat NU is able to create harmonious relationships and strengthen the foundation of Islamic life in Indonesia through various activities.